Antifungal Activities of Ageratum conyzoides L. Extract against Rice Pathogens Pyricularia oryzae Cavara and Rhizoctonia solani Kühn - Cuong C. Nguyen (MDPI AG, 2021)
Blast disease and sheath blight disease caused by infection with Pyricularia oryzae and Rhizoctonia solani, respectively, are serious fungal diseases in paddy fields. Although synthetic fungicides have been used to control these diseases, the development of ecologically friendly alternatives is required because fungicides can cause health problems and environmental pollution. Natural herbs possessing antifungal activities are among the candidates as alternatives. Ageratum conyzoides is known to contain antifungal compounds, such as precocene II and polymethoxyflavones. Here, we report the antifungal activities of five compounds isolated after ethanol extraction from Ageratum conyzoides against Pyricularia oryzae and Rhizoctonia solani in vitro. Further, we demonstrated the protective effect of the extract on rice from Pyricularia oryzae infection by field trial testing in a shaded net-house.